Preparation, characterization, and evaluation of bedaquiline fumarate: ascorbic acid co-crystals with enhanced pharmaceutical and physicochemical properties - Shital D. Godse; Ranjit B. Mohare; Vishal P. Zambre; Vidhya K. Bhusari; Minal Ghante (Future Journal of Pharmaceutical Sciences)
Abstract Background Bedaquiline fumarate (BDQ) is an anti-tubercular Biopharmaceutics Classification System (BCS class-II) drug & it has very less solubility. Therefore, an effort has been made to prepare the bedaquiline fumarate co-crystal to improve its physicochemical and pharmaceutical characteristics. Results Using the solvent evaporation method, the drug bedaquiline fumarate and co-former ascorbic acid (AA) were co-crystallized. A series of analytical techniques, i.e., X-ray diffraction (XRD), Fourier transformation infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), and UV spectroscopy, etc., were used for the analysis of co-crystal to predict co-crystal formation by molecular docking. Micromeritic study and tablet formulation were done of bedaquiline fumarate and co-crystal formulation (1:2) batch. A permeability study was conducted on the chicken ileum. Conclusion Active pharmaceutical ingredients can co-crystallize with other small molecules or co-formers to create new solid dosage forms that have better physicochemical characteristics than pure drugs. 22 co-formers were screened with the drug, ascorbic acid was selected as a co-former because it has a binding energy of − 1.2 kcal/mol, two hydrogen bonds are formed, and it becomes readily soluble in water. This study indicated that ascorbic acid as a co-former can increase the dissolution profile of bedaquiline fumarate by the co-crystallization approach.